Asymptotic distribution of sample covariance determinant - Djauhari, Maman A. (Faculty of Science, UTM, 2009)
Under normality, an asymptotic distribution of sample covariance determinant will be derived. We show that this asymptotic distribution is more applicable in practice than the classical one. This will justify its usefulness in inferential study and other applications in a more comprehensive and accurate manner